2020
DOI: 10.22271/ortho.2020.v6.i2d.2043
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of extra-articular distal tibia fractures managed by intramedullary nailing vs locking plate

Abstract: Introduction: Distal tibial fractures are common long bone fractures that occur mainly due to a high velocity trauma. These are difficult to treat because of its subcutaneous location and poor blood supply. Many studies have been published on modalities of treatment of distal tibia fractures. Available options are Intramedullary nails, locking plates and external fixators. The aim of our study was to compare intramedullary interlocking (IMIL) nailing and locking plate (LP) for the treatment of these fractures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In our study, the mean operative time in the MIPO group was 63.8±10. 13 [18] also reported comparable scores between the two groups. Daolagupu et al also showed similar functional outcomes between the two groups, but using different functional outcome criteria (Johner and Wruh's criteria).…”
Section: Discussionmentioning
confidence: 64%
“…In our study, the mean operative time in the MIPO group was 63.8±10. 13 [18] also reported comparable scores between the two groups. Daolagupu et al also showed similar functional outcomes between the two groups, but using different functional outcome criteria (Johner and Wruh's criteria).…”
Section: Discussionmentioning
confidence: 64%